Konsep pendidikan iman pada anak menurut Muhammad Nur Abdul Hafizh Suwaid - Marwanto Marwanto; Happy Susanto; Anip Dwi Saputro (Universitas Muhammadiyah Ponorogo, 2020)
This study aims to explain and describe the concepts and methods of faith education in children according to Muhammad Nur Abdul Hafizh Suwaid. The research approach used in this research is library (literature) research presented qualitatively, by analyzing books or texts related to the thoughts of Muhammad Nur Abdul Hafizh Suwaid about faith education for children. The main reference source used in this study is the work of Muhammad Nur Abdul Hafizh Suwaid in his book entitled “mendidik anak bersama nabi”. The results of this study suggest that: faith education in children according to Muhammad Nur Abdul Hafizh Suwaid should be taught to children from childhood, because this phase is the longest phase in the child's life journey, and at this time is a golden period. Childhood has the advantages of being active, pure and natural. As for the method of faith education in children, according to Muhammad Nur Abdul Hafizh Suwaid, it can be done by: (a) dictating to children with tauhid sentences; (b) love Allah and feel watched over by Him, ask Him for help, and faith in qadha and qadar; (c) instill love for the Prophet; (d) teach al-Qur’an to children; and (e) instill a strong and self-sacrificing aqidah with it.